Clinical outcome of concomitant vs interrupted BRAF inhibitor therapy during radiotherapy in melanoma patients - Hecht, Markus; Meier, Friedegund; Zimmer, Lisa; Polat, Bülent; Loquai, Carmen; Weishaupt, Carsten; Forschner, Andrea; Gutzmer, Ralf; Utikal, Jochen; Goldinger, Simone M.; Geier, Michael; Hassel, Jessica C.; et al. (British journal of cancer, 2018)
Concomitant radiation with BRAF inhibitor (BRAFi) therapy may increase radiation-induced side effects but also potentially improve tumour control in melanoma patients. A total of 155 patients with BRAF-mutated melanoma from 17 European skin cancer centres were retrospectively analysed. Out of these, 87 patients received concomitant radiotherapy and BRAFi (59 vemurafenib, 28 dabrafenib), while in 68 patients BRAFi therapy was interrupted during radiation (51 vemurafenib, 17 dabrafenib). Overall survival was calculated from the first radiation (OSRT) and from start of BRAFi therapy (OSBRAFi). The median duration of BRAFi treatment interruption prior to radiotherapy was 4 days and lasted for 17 days. Median OSRT and OSBRAFi in the entire cohort were 9.8 and 12.6 months in the interrupted group and 7.3 and 11.5 months in the concomitant group (P=0.075/P=0.217), respectively. Interrupted vemurafenib treatment with a median OSRT and OSBRAFi of 10.1 and 13.1 months, respectively, was superior to concomitant vemurafenib treatment with a median OSRT and OSBRAFi of 6.6 and 10.9 months (P=0.004/P=0.067). Interrupted dabrafenib treatment with a median OSRT and OSBRAFi of 7.7 and 9.8 months, respectively, did not differ from concomitant dabrafenib treatment with a median OSRT and OSBRAFi of 9.9 and 11.6 months (P=0.132/P=0.404). Median local control of the irradiated area did not differ in the interrupted and concomitant BRAFi treatment groups (P=0.619). Skin toxicity of grade ≥2 (CTCAE) was significantly increased in patients with concomitant vemurafenib compared to the group with treatment interruption (P=0.002). Interruption of vemurafenib treatment during radiation was associated with better survival and less toxicity compared to concomitant treatment. Due to lower number of patients, the relevance of treatment interruption in dabrafenib treated patients should be further investigated. The results of this analysis indicate that treatment with the BRAFi vemurafenib should be interrupted during radiotherapy. Prospective studies are desperately needed.
Gesehen am 28.04.2020